THE DESTROYED MINARET OF THE UMAYYAD MOSQUE OF ALEPPO, THE SURVEY OF THE ORIGINAL STATE - Fangi, Gabriele; Wahbeh, Wissam (European Scientific Journal, ESJ, 2014)
This paper discusses the spherical photogrammetry as a metric documentation technique applied in the field of architectural and archeological heritage. the mentioned technique can obtain dimensions and shapes of the architectural geometry which could be used to create 3D models, suitable for reconstruction and restoration. The applications shown in this paper is the survey of the Minaret of the Umayyad Mosque of Aleppo in the UNESCO heritage site of ancient city of Aleppo. The Minaret was destroyed during the current civil war, but fortunately a metric photographic documentation was effected three years before for many important monuments inside World heritage sites in Syria, and this minaret is one of them. This metric documentation could be a very useful reference for a future reconstruction or restoration of those structures.